2003
DOI: 10.1128/jvi.77.21.11332-11346.2003
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus (MV) Nucleoprotein Binds to a Novel Cell Surface Receptor Distinct from FcγRII via Its C-Terminal Domain: Role in MV-Induced Immunosuppression

Abstract: During acute measles virus (MV) infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 63 publications
5
79
0
Order By: Relevance
“…Avota et al showed that MV envelope proteins inhibit the CD3/CD28-induced proliferation of T cells by affecting the phosphatidylinositol 3-/Akt kinase pathway (5). The nucleocapsid (N) protein of MV was shown to exhibit immunosuppressive activities by binding the Fc␥ receptor type II on antigen-presenting cells (30) or the N protein receptor expressed on a large variety of cell types (28). These studies were performed in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Avota et al showed that MV envelope proteins inhibit the CD3/CD28-induced proliferation of T cells by affecting the phosphatidylinositol 3-/Akt kinase pathway (5). The nucleocapsid (N) protein of MV was shown to exhibit immunosuppressive activities by binding the Fc␥ receptor type II on antigen-presenting cells (30) or the N protein receptor expressed on a large variety of cell types (28). These studies were performed in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…MV and the F/H complex have a number of effects on lymphocytes, including cell cycle arrest at the G 0 /G 1 phase, reduced expression and activity of cyclin-dependent kinase complexes, delayed degradation of p27Kip, and inhibition of actin remodeling, T-cell polarization, and TcR clustering to the site of T-cell/antigen-presenting cell contact (35,104,108,130). In addition to the MV F/H protein complex, the MV nucleoprotein has been shown to inhibit antigen-specific or mitogen-induced T-cell proliferation, presumably via binding of a putative nucleoprotein binding receptor expressed upon T-cell activation (78,91,92).…”
Section: (And Other Morbilliviruses)mentioning
confidence: 99%
“…A short sequence in the MeV N tail (residues 489 to 506) folds into a dynamic helical structure that is stabilized by binding of the viral phosphoprotein that carries the viral RNA-dependent RNA polymerase (12,13,16). The N tail is also involved in binding host proteins, such as hsp70 (5,26) and interferon regulatory factor 3 (14,15). So far, the location of the N tail on the helix is not known, although it is usually shown on the outside in cartoons that illustrate transcription and replication of paramyxoviruses (see Fig.…”
mentioning
confidence: 99%